The role of intra-session exercise sequence in the interference effect: A systematic review with meta-analysis - Eddens, L.; van Someren, K.; Howatson, G. (Sports Medicine, 2018)
Background: There is a necessity for numerous sports to develop strength and aerobic capacity simultaneously, placing a significant demand upon the practice of effective concurrent training methods. Concurrent training requires the athlete to perform both resistance and endurance exercise within a training plan. This training paradigm has been associated with an `interference effect`, with attenuated strength adaptation in comparison to that following isolated resistance training. The effectiveness of the training programme rests on the intricacies of manipulating acute training variables, such as exercise sequence. The research, in the most part, does not provide a clarity of message as to whether intra-session exercise sequence has the potential to exacerbate or mitigate the interference effect associated with concurrent training methods. Objective: The aim of the systematic review and meta-analysis was to assess whether intra-session concurrent exercise sequence modifies strength-based outcomes associated with the interference effect. Methods: Ten studies were identified from a systematic review of the literature for the outcomes of lower-body dynamic and static strength, lower-body hypertrophy, maximal aerobic capacity and body fat percentage. Each study examined the effect of intra-session exercise sequence on the specified outcomes, across a prolonged (=5 weeks) concurrent training programme in healthy adults. Results: Analysis of pooled data indicated that resistance-endurance exercise sequence had a positive effect for lower-body dynamic strength, in comparison to the alternate sequence (weighted mean difference, 6.91% change; 95% confidence interval 1.96, 11.87 change; p = 0.006), with no effect of exercise sequence for lower-body muscle hypertrophy (weighted mean difference, 1.15% change; 95% confidence interval -1.56, 3.87 change; p = 0.40), lower-body static strength (weighted mean difference, -0.04% change; 95% confidence interval -3.19, 3.11 change; p = 0.98), or the remaining outcomes of maximal aerobic capacity and body fat percentage (p > 0.05). Conclusion: These results indicate that the practice of concurrent training with a resistance followed by an endurance exercise order is beneficial for the outcome of lower-body dynamic strength, while alternating the order of stimuli offers no benefit for training outcomes associated with the interference effect.